Predictors of Educational Outcomes of Students with Multiple Disabilities: Results from a National Study - Kymberly Bowlen; Kristen Osiniak; Tyler Syms; Karen H Larwin (International Journal of Evaluation and Research in Education (IJERE), 2018)
Parents, siblings, and peers have an immeasurable effect on shaping children into who they become as individuals. Many factors, such as one’s relationships with these individuals, may have lasting effects on the educational and vocational outcomes of children who have multiple disabilities. The purpose of the present study is to investigate the relationships of children with multiple disabilities, as well as their perceptions regarding their educational experiences to determine the effects these factors may have on their future outcomes. The goal of the present study is to determine how potential correlations may influence children with multiple disabilities during transition and vocational programs, as well as their outcomes in life beyond formal schooling.